1993
DOI: 10.1128/aac.37.7.1468
|View full text |Cite
|
Sign up to set email alerts
|

Bioequivalence of oral and intravenous ofloxacin after multiple-dose administration to healthy male volunteers

Abstract: The bioequivalence of oral and intravenous ofloxacin was investigated after the administration of multiple doses of 400 mg every 12 h to 20 healthy male volunteers in a randomized, crossover, open-label study. Ofloxacin concentrations in plasma were evaluated after 4 days of oral or intravenous (1-h infusion) dosing with a 3-day wash-out period between regimens. As expected, delivery to the systemic circulation took slightly longer after the oral dosing (time to maximum concentration of drug in serum of 1.7 h)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

1994
1994
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Elimination was assumed to be linear and first order. This model has been successfully applied to characterize the pharmacokinetics of levofloxacin in HIV-infected subjects and the pharmacokinetics of ofloxacin in healthy volunteers (2,5). Estimated pharmacokinetic parameters of levofloxacin included the area under the plasma concentration-time curve (AUC 0-t ) as measured by the trapezoidal summation method; AUC 0-ϱ calculated as AUC 0-last ϩ Cp last /k el , where Cp last is the last measurable plasma concentration and k el is the terminal elimination rate constant calculated as the slope of the terminal log-linear phase of the plasma concentration-time profile; apparent total body clearance (CL/F) calculated as dose/AUC 0-ϱ for a single dose and as dose/AUC 0-8 at steady state; and apparent volume of distribution (V/F) calculated as CL/F ⅐ (MRTϪT max /2), where MRT refers to the mean residence time following drug administration.…”
Section: Methodsmentioning
confidence: 99%
“…Elimination was assumed to be linear and first order. This model has been successfully applied to characterize the pharmacokinetics of levofloxacin in HIV-infected subjects and the pharmacokinetics of ofloxacin in healthy volunteers (2,5). Estimated pharmacokinetic parameters of levofloxacin included the area under the plasma concentration-time curve (AUC 0-t ) as measured by the trapezoidal summation method; AUC 0-ϱ calculated as AUC 0-last ϩ Cp last /k el , where Cp last is the last measurable plasma concentration and k el is the terminal elimination rate constant calculated as the slope of the terminal log-linear phase of the plasma concentration-time profile; apparent total body clearance (CL/F) calculated as dose/AUC 0-ϱ for a single dose and as dose/AUC 0-8 at steady state; and apparent volume of distribution (V/F) calculated as CL/F ⅐ (MRTϪT max /2), where MRT refers to the mean residence time following drug administration.…”
Section: Methodsmentioning
confidence: 99%
“…However, because preliminary studies indicated that the pharmacokinetic properties of LVFX in healthy volunteers and presumably also in mice were very similar to those of OFLO (14) and because there is no evidence that the adverse reactions to fluoroquinolones are correlated with their anti-DNA gyrase activities, it is likely that the maximal clinically tolerated dosage of LVFX is similar to that of OFLO, i.e., 800 mg per day (5,9). Since the half-life of OFLO in humans (2,8,24) is significantly longer than that in mice (19), there is a very significant accumulation effect after multiple doses in healthy human volunteers (8) but probably not in mice; therefore, to extrapolate the results of the mouse experiments for the treatment of humans, it is appropriate to take into account the pharmacokinetic data for OFLO and LVFX in humans after multiple doses. Because the area under the concentration-time curve, 48.8 g ⅐ h/ml, for mice treated with a single dose of OFLO at 150 mg/kg (19) is very similar to the area under the concentration-time of 48.1 (8) or 41.20 Ϯ 6.98 (2) g ⅐ h/ml for humans treated with multiple doses of OFLO at 400 mg every 12 h, it is reasonable to estimate that in terms of the area under the concentration-time curve, OFLO at 300 mg/kg in mice is equivalent to OFLO at 800 mg, or the maximal clinically tolerated dosage, in humans.…”
Section: Discussionmentioning
confidence: 99%
“…The acids were thiopental and nifedipine (Nguyen et al, 1996;Ke et al, 2012). The neutrals were digoxin and artemether, and the zwitterion was ofloxacin (Sumner and Russell, 1976;Flor et al, 1993;Lin et al, 2016). The Schmitt and PK-Sim Standard methods recommended the use of membrane affinity (logMA) in place of logP (Willmann et al, 2005;Schmitt, 2008).…”
Section: Downloaded Frommentioning
confidence: 99%
“…(Sumner and Russell, 1976), and (E) ofloxacin (400 mg, i.v.) (Flor et al, 1993). Dots indicate means, and error bars indicate S.D.…”
Section: Downloaded Frommentioning
confidence: 99%